2022
DOI: 10.1177/13623613221109717
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and intolerance of uncertainty predict somatic symptoms in autistic and non-autistic adults

Abstract: Autistic people experience heightened rates of physical health problems but may also experience elevated levels of somatic symptoms (e.g. pain, headache, gastrointestinal symptoms) due to psychological factors which are common in autism. This online study sought to compare rates of somatic symptoms (Patient Health Questionnaire-15) in older adolescents and adults who were autistic ( n = 51), non-autistic ( n = 119) and who suspected they were autistic ( n = 32), while controlling for health conditions. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…In 2022, Larkin et al [ 41 ] conducted an online study where somatic symptom rates, measured by the Patient Health Questionnaire-15, were compared among 202 older adolescents and adults (F = 146; M = 48; other = 8; mean age = 31.33 ± 12.90) with diagnosed ASD (N = 51), self-suspected ASD (N = 32), and without ASD (N = 119) while accounting for medical conditions. The authors investigated possible risk factors for somatic symptoms such as alexithymia, interoceptive sensibility, and intolerance of uncertainty with the General Alexithymia Factor Score, Body Awareness Questionnaire, and Intolerance of Uncertainty Scale, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Larkin et al [ 41 ] conducted an online study where somatic symptom rates, measured by the Patient Health Questionnaire-15, were compared among 202 older adolescents and adults (F = 146; M = 48; other = 8; mean age = 31.33 ± 12.90) with diagnosed ASD (N = 51), self-suspected ASD (N = 32), and without ASD (N = 119) while accounting for medical conditions. The authors investigated possible risk factors for somatic symptoms such as alexithymia, interoceptive sensibility, and intolerance of uncertainty with the General Alexithymia Factor Score, Body Awareness Questionnaire, and Intolerance of Uncertainty Scale, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, besides the female gender, physical and mental health issues, alexithymia, and intolerance of uncertainty also predicted somatic symptoms. No significant predictive effect was found, however, for interoception or the presence of an ASD diagnosis [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, psychological concepts closely related to autistic-like features can provide part of an explanation. As such, a recent study found that alexithymia (difficulty in identifying and describing own emotions) and intolerance of uncertainty were predictive of somatic symptoms in both autistic and non-autistic adults, regardless of autism status (Larkin et al, 2022). It is, however, very difficult to disentangle these two predictors from autistic-like features.…”
Section: Discussionmentioning
confidence: 99%
“…A new finding of this study is that child IU was the link between somatic symptoms and anxiety, which is an association that was found in autistic adults. Similar to SOR, the hypothesis is that physical symptoms could trigger IU, which can generalize and lead to anxiety (Larkin et al, 2023). Our network findings, however, are not causal or directional, and therefore reciprocal relationships may also be at play, that is, anxiety triggering SOR or somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%